P131 Serum Proteomics and Intestinal Ultrasound Differentiates Fibrostenotic and Inflammatory Crohn's Disease. (27th May 2021) - Lu, C; Filyk, A; Mainoli, B; de Almeida, L; Novak, K; Panaccione, R; Hirota, S; Dufour, A
Abstract: Background: Fibrostenotic Crohn's disease (CD) is a challenging phenotype often leading to surgical resection. Easily accessible and cost-effective diagnostic tools are needed to advance precision medicine to manage fibrostenotic CD patients. To date, there are no biomarkers that can discriminate stricturing CD from other phenotypes. Early studies suggest that protein biomarkers identified from serum proteomics may differentiate CD subtypes. Utilizing intestinal ultrasound (IUS), which readily detects strictures, the serum of patients with and without strictures was collected for proteomic characterization. Methods: All consecutive CD patients attending outpatient appointments received IUS, and CT (computed tomography)/MR (magnetic resonance) within 6 months of study inclusion. Strictures were defined as a fixed segment of the ileum with increased bowel wall thickness (BWT) and luminal apposition with or without prestenotic dilation. Thirty two patients with ileal strictures were matched with CD patients without strictures (inflammatory behaviour). Serum of patients were collected for quantitative shotgun proteomics using liquid chromatography and tandem-mass spectrometry (LC-MS/MS). Results: 64 patients in the stricture group had a significantly greater mean ileal bowel wall thickness (7.5 mm) compared to the inflammatory group (4.5mm, p = 0.02). A distinct and statistically significant protein signature was discovered between both patient populations. In the stricture group: plexin-A2, CD5 antigen-like protein, neogenin and dystonin were found, while in the non-strictured patients, matrix metalloproteinase 16, C-reactive protein, vinculin and apolipoprotein C-III were detected. Using Metascape and STRING-db, gene ontology and reactome pathway analyses, we identified enrichment of B cell differentiation and muscle contraction in the stricture patients, whereas in the non-stricture group, an enrichment for high-density lipoprotein remodeling, innate immune system and calcium ion transport were found. Conclusion: We identified a unique protein signature that could robustly distinguish CD strictures from inflammatory phenotypes. This innovative diagnostic preliminary protein panel will be further expanded and validated in inflammatory and fibrostenotic CD populations, potentially allowing for future clinical decision optimization.